Measuring Acculturation of Pakistani Women: A Psychometric Evaluation of Urdu Version of the Short Acculturation Scale - Dorothy N. S Chan; Winnie K. W So (Elsevier, 2019)
Objectives: The purpose of the study was to translate and validate the psychometric properties of the Short Acculturation Scale-Urdu version (SAS-U) for Pakistani women in Hong Kong. Methods: This is a methodological study, and a convenience sample of 263 Pakistani women was recruited to participate in the study. The SAS was translated from English to Urdu using forward and backward translation and reviewed by an expert panel for semantic equivalence and content validity. Face validity was done by five bilingual Pakistani women. Construct validity was established by confirmatory factor analysis (CFA). Convergent validity was examined by the bivariate correlation of proxy indicators such as language preference, with the overall and subscales of SAS-U. Reliability was established by internal consistency and test-retest reliability. IBM SPSS Statistics for Windows version 22.0 and LISREL version 8.80 were used for data analysis. Results: The translated SAS-U had good content validity and face validity. CFA revealed that the second-order model with three first-order factors and the results was supported by the following indices: root mean square error of approximation = 0.055, standardized root mean square residual = 0.031, χ2/df = 1.80, nonnormed fit index = 0.99, and comparative goodness-of-fit index = 1.00. Language preference correlated significantly with the overall and subscales of SAS-U (r > 0.6, P < 0.01). SAS-U demonstrated high internal consistency (Cronbach's alpha = 0.96) and acceptable test-retest reliability (weighted kappa = 0.68-0.93). Conclusions: The results provide support for the psychometric properties of the SAS-U - it is a reliable and valid instrument for measuring levels of acculturation among Pakistani women in Hong Kong.